1997
DOI: 10.1007/s004390050606
|View full text |Cite
|
Sign up to set email alerts
|

ACP1 and human adaptability 2. Association with season of conception

Abstract: We have studied the pattern of association between the season of conception and cytosolic low molecular weight phosphotyrosine phosphatase (ACP1) genetic polymorphism in 329 consecutively newborn infants from the population of Penne and 361 consecutively newborn infants from the population of Rome. In addition, 329 mothers were studied in the population of Penne. A concordant, highly significant association was observed in the two populations between ACP1 parameters and the season of conception of newborn infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Further evidence in favor of an important role of ACP1 in the adaptation to a cold environment is suggested by the increased proportion of the ACP1*A allele in infants conceived in the cold season (Gloria-Bottini et al, 1996a, 1997b. This hypothesis is consistent with functions recently suggested for ACP1.…”
Section: Ada-acp1 Associationsupporting
confidence: 75%
“…Further evidence in favor of an important role of ACP1 in the adaptation to a cold environment is suggested by the increased proportion of the ACP1*A allele in infants conceived in the cold season (Gloria-Bottini et al, 1996a, 1997b. This hypothesis is consistent with functions recently suggested for ACP1.…”
Section: Ada-acp1 Associationsupporting
confidence: 75%
“…Our data have shown that among mothers carrying the ACP1*A allele (the allele showing the lowest activity), the proportion of newborns carrying this allele is higher in those conceived in the first months of the year than in those conceived in subsequent periods (4). Owing to its functions as a phosphotyrosine phosphatase and as an FMN phosphatase, ACP1 phenotypes with low enzymatic activity could be able to enhance the metabolic rate and would therefore be advantageous in a cold environment.…”
Section: Discussionmentioning
confidence: 79%
“…This may be connected both to the effect on the insulin receptor (29) and to the effect on the concentration of FMN, suggesting increased metabolic activity in carriers of the low-activity ACP1 genotypes. Our group has shown an increased frequency of the ACP*A allele in infants conceived in the cold season (3,4).…”
Section: The Acp1 Polymorphismmentioning
confidence: 85%
See 1 more Smart Citation
“…More recent, interest has been centred on the relationship between the season of birth and performance in school, sports, and in public and scientific sectors (Dudink, 1994;Azevedo et al, 1995;Holmes, 1995;Gloria-Bottini, 1996). Some genetic parameters bear a relationship with the season of the conception (Gloria- Bottini et al, 1997;Bottini et al, 2001;Bjorksten, 1999) suggesting that the population of zygotes conceived in a given season reproduces the pattern of parental gene combinations more successful in reproductive activity during that season.…”
Section: Discussionmentioning
confidence: 99%